COMPUTER AIDED DESIGN AND IMPLEMENTATION OF CONVERTER CIRCUITS APPLIED FOR PHOTOVOLTAIC SYSTEM - Z. M. Kubba; K. AL-shara; E. AL-Shakarchi (Journal of Engineering, 2024)
This research intents to design and laboratory implementation of a power electronic converter, which is useful for home applications, industrial, communications, street light and water pumping using solar cell source. The design is based on a step up boost DC/DC converter followed by a full wave SPWM inverter. The nominal power rating is 1.25kW and can operate from any DC source such as DC battery besides fuel cells. The system which consists of the following stages (PV, converter, inverter, DC link, filter and snubber circuit), is designed primarily with a general module depending on Orcad PSPICE program to produce power output nearly 1.25kVA at 50Hz with a pure sinewave output for both voltage and current. After designing and simulating this system, the intended SPWM inverter are built experimentally to compare its results with the simulated one.